Kepastian Hukum Kekuatan Eksekutorial Sertipikat Hak Tanggungan Elektronik (Studi Peraturan Menteri ATR/KBPN Nomor 5 Tahun 2020) - Usak Usak (Universitas Batanghari Jambi, 2023)
The National Land Agency may now provide their dependents access to online services thanks to Ministerial Regulation No. 5 of 2020 from ATR/KBPN. The purpose of this paper is to evaluate the progress made toward implementing the requirements of ATR/KBPN ministerial order Number 5 of 2020, namely the Electronic Dependent Rights Certificate and the mechanisms for electronic inheritance of Dependent Rights. The norms of the law are observed in this kind of investigation. According to the findings, ATR/KBPN Regulation No. 5 of 2020 governs the procedure for adding dependents to the Electronic Dependent Rights System. Neither UUHT nor Permen ATR/KBPN No. 5 of 2020 prohibits the use of EDRs. It is the author's contention that, as Electronic Dependent Rights do not have any kind of inherent priority, Article 54 of the ITE Law prohibits their use as executory proof. The Electronic Dependent Rights Certificate does not provide any further clarity or legal protection for creditors and borrowers.